2017
DOI: 10.1021/acscatal.7b02278
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Hydroxycarbonylation of Pentenoic Acids. Computational and Experimental Studies on the Catalytic Selectivity

Abstract: The palladium-catalyzed conversion of (bio)pentenoic acid isomers (PEAs) occurs with high activity and selectivity to adipic acid (ADA) in the presence of the diphosphine ligand L 2 = 1,2-bis[(di-tert-butyl)phosphinomethyl]benzene (DTBPX) and an acid cocatalyst. Using density functional theory (DFT) calculations, we show that the active catalyst ([L 2 Pd II -H] + ) isomerizes the PEAs to their equilibrium mixture, from which selective carbonylation and hydrolysis results in the ADA product. Hydrolysis is the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 81 publications
(150 reference statements)
0
27
0
Order By: Relevance
“…Other commonly used bisphosphine ligands, such as DPPP L4, DPPB L5 and BINAP L6, did not exhibit any catalytic activity. Interestingly, when testing 1,2-bis[(di-tert-butyl)phosphino-methyl]benzene (L7, d t bpx), [10] which is used by Lucite International to produce methyl methacrylate and was also employed by Drent for carbonylation of 1,3-butadiene, [11] the major product is still 5 a; however, in addition 17 % of C6-diacids are achieved with high selectivity (95 %) for linear adipic acid. Unfortunately, using ligands L8 and L9 in which the di-tert-butylphosphine units are replaced with more stable di-phenylphosphine or diadamantyl units did not give better results.…”
mentioning
confidence: 99%
“…Other commonly used bisphosphine ligands, such as DPPP L4, DPPB L5 and BINAP L6, did not exhibit any catalytic activity. Interestingly, when testing 1,2-bis[(di-tert-butyl)phosphino-methyl]benzene (L7, d t bpx), [10] which is used by Lucite International to produce methyl methacrylate and was also employed by Drent for carbonylation of 1,3-butadiene, [11] the major product is still 5 a; however, in addition 17 % of C6-diacids are achieved with high selectivity (95 %) for linear adipic acid. Unfortunately, using ligands L8 and L9 in which the di-tert-butylphosphine units are replaced with more stable di-phenylphosphine or diadamantyl units did not give better results.…”
mentioning
confidence: 99%
“…[100] Recently, Zhao and co-workers proposed another novel two-step process for the synthesis of AA from GVL. [6] Firstly, GVL was distilled over ZSM-5 catalyst to obtain a mixture of PEAs with a yield of 96 %. [101] Then, in the presence of CO and water, the mixture of PEAs were transformed into AA using a Pd diphosphine catalyst by a tandem isomerization-hydroxycarbonylation reaction in the homogeneous media with an overall yield of 48 % (Scheme 11a).…”
Section: Preparation Of Aa From Gvlmentioning
confidence: 99%
“…[1b] Furthermore, another serious drawback of this pathway is producing approximately 10 % of annual global emissions of the greenhouse gas N 2 O. [6] Although several new catalytic systems have been reported, the feedstock still relies on nonrenewable petroleum-derived benzene. [7] Therefore, it remains urgent to design and develop renewable resources for the synthesis of AA to replace the traditional fossil resources.…”
Section: Introductionmentioning
confidence: 99%
“…Even the most stable conjugated alkene can undergo this transformation. Notably, pentenoic acids can be obtained from biomass via γ‐valerolactone . It was demonstrated that by using the above described ALPHA‐process catalyst in the methoxycarbonylation of pentenoic acid, the corresponding dimethyl adipate ( 14 ) was obtained with 97 % selectivity and full conversion of the substrate .…”
Section: Cooperative Catalysismentioning
confidence: 99%